Economics of water management in agriculture - Bournaris, Thomas (CRC Press, 2015)
This book includes a set of papers from distinguished scholars who critically examine economic issues relating to the relationship between water and agriculture, with a special focus on irrigation. Employing state of the art methodologies, they address the most relevant issues in water policy. The volume offers a wide spectrum of innovative approaches and original and relevant cases with a focus on irrigated European agriculture. The topics analyzed include qualitative and quantitative issues, water markets, demand analysis, economic analysis, implementation of economic issues.